The Gender Gap in Entrepreneurship: Not Just a Matter of Personality - Marco Caliendo; Frank Fossen; Alexander Kritikos; Miriam Wetter (Center for Economic Studies and ifo Institute (CESifo), 2014)
Why do entrepreneurship rates differ so markedly by gender? Using data from a large, representative German household panel, we investigate to what extent personality traits, human capital, and the employment history influence the start-up decision and can explain the gender gap in entrepreneurship. Applying a decomposition analysis, we observe that the higher risk aversion among women explains a large share of the entrepreneurial gender gap. We also find an education effect contributing to the gender difference. In contrast, the Big Five model and the current employment state have effects in the opposite direction, meaning that the gender gap in entrepreneurial entry would be even larger if women had the same scores and the same employment status as men.
Keywords: L26; J16; D81; J24; M13; 330; entrepreneurship; gender gap; personality; decomposition analysis